Evaluation of type-B RR dimerization in poplar: A mechanism to preserve signaling specificity?. (December 2021) - Djeghdir, I.; Chefdor, F.; Bertheau, L.; Koudounas, K.; Carqueijeiro, I.; Lemos Cruz, P.; Courdavault, V.; Depierreux, C.; Larcher, M.; Lamblin, F.; Héricourt, F.; Glévarec, G.; et al.
Highlights: Dimerization map of type-B RRs from poplar clone "Dorskamp" by Y2H and BiFC assays. Type-B RRs are all able to homo-dimerize. Hetero-dimerization between type-B RRs is not always possible. Abstract: Plants possess specific signaling pathways, such as the MultiStep Phosphorelay (MSP), which is involved in cytokinin and ethylene sensing, and light, drought or osmotic stress sensing. These MSP comprise histidine-aspartate kinases (HKs) as receptors, histidine phosphotransfer (HPts) proteins acting as phosphorelay proteins, and response regulators (RRs), some of which act as transcription factors (type-B RRs). In previous studies, we identified partners of the poplar osmosensing signaling pathway, composed of two HKs, three main HPts, and six type-B RRs. To date, it is unresolved as to how cytokinin or osmotic stress signal specificity is achieved in the MSP in order to generate specific responses. Here, we present a large-scale interaction study of poplar type-B RR dimerization. Using the two-hybrid assay, we were able to show the homodimerization of type-B RRs, the heterodimerization of duplicated type-B RRs, and surprisingly, a lack of interaction between some type-B RRs belonging to different duplicates. The lack of interaction of the duplicates RR12-14 and RR18-19, which are involved in the osmosensing pathway has been confirmed by BiFC experiments. This study reveals, for the first time, an overview of type-B RR dimerization in poplar and makes way for the hypothesis that signal specificity for cytokinin or osmotic stress could be in part due to the fact that it is impossible for specific type-B RRs to heterodimerize.